FINANCIAL PYRAMIDS IN UZBEKISTAN: CRIMINALISATION, DETECTION, AND THE PREVENTIVE ROLE OF FINANCIAL INSTITUTIONS - Sardor Khushvaktov (International Journal of Business, Law and Political Science, 2026)
Objective: This article argues that effective prevention requires criminal law to operate together with AML/CFT controls, anti-fraud systems, transaction monitoring, inter-agency coordination, early asset restraint and consumer protection. Method: The study combines doctrinal analysis of Uzbek legislation, risk-based compliance analysis, a limited comparison with Kazakhstan, Russia and the United States, and review of publicly documented enforcement episodes. Results: The principal gaps are the absence of published pyramid-specific typologies, a consolidated official warning mechanism, coordinated real-time response and a victim-oriented asset-recovery framework. Priority reforms should therefore focus on early detection and interruption of collection flows rather than on increasing punishment. Novelty: It proposes a legal-economic test for distinguishing pyramids from lawful commercial and investment models and identifies the transactional indicators available to banks and payment organisations.